Double-Walled Tubular Heusler-Type Platinum-Ruthenium Phosphide as All-pH Hydrogen Evolution Reaction Catalyst Outperforming Platinum and Ruthenium - Hong, Yongju; Cho, Seong Chan; Kim, Soobean; Jin, Haneul; Seol, Jae Hun; Lee, Tae Kyung; Ryu, Jong-kyeong; Tomboc, Gracita M.; Kim, Taekyung; Baik, Hionsuck; Choi, Changhyeok; Jo, Jinhyoung; et al. (Wiley-VCH Verlag, 2024)
Nanostructured ionic compounds have driven major technological advancements in displays, photovoltaics, and catalysis. Current research focuses on refining the chemical composition of such compounds. In this study, a strategy for creating stoichiometrically well-defined nanoscale multiple-cation systems, where the atomically precise structure maximizes the synergistic cooperation between cations at the atomic scale is reported. The unprecedented construction of Heusler-type PtRuP2 double-walled nanotubes through sequential anion/cation exchange reactions is demonstrated. The PtRuP2 catalyst exhibits record-high catalytic performance and durability for the hydrogen evolution reaction (HER) in alkaline electrolytes and anion-exchange membrane water electrolyzers. The investigations highlight the crucial role of Pt/Ru dual centers, providing multiple active sites that accelerate the HER kinetics within a single phosphide material, in the sequential operation of H2O activation/dissociation at Ru and H2 production at adjacent Pt sites. These findings open new avenues for optimizing ionic compound-based HER electrocatalysts, offering platinum-metal alternatives in acidic and alkaline media. The atomically well-localized multimetal-based ionic compound PtRuP2 is an important class of materials for maximizing the synergistic interactions between catalytic centers with disparate roles. This feature is particularly beneficial for addressing the challenging kinetics of the non-acidic hydrogen evolution reaction, thereby promoting the successful commercialization of anion-exchange membrane water electrolyzers. image